Development of e-health education system using IoT and web-based application for people living with diabetes - Norhashimah, Mohd Saad; Abdullah, Abdul Rahim; Shair, Ezreen Farina; Kandaya, Shaarmila; Haznan, Nur Nasrien Syazwani; Mohamad Basir, Muhammad Sufyan Safwan (Politeknik Mukah, 2025)
Diabetes is a growing concern globally, including in Malaysia, where its prevalence continues to rise, straining healthcare resources and impacting individuals' well-being. The inadequacy of ongoing support and limited consultation time exacerbates poor self-care practices, leading to uncontrolled blood sugar levels and adverse health outcomes. To address these challenges, this project focuses on developing the e-Health Medical Connecting Platform for Diabetes Care, named Medicolink, which integrates web-based resources with hardware, sensor capabilities and IoT technology. Through this innovative approach, the aim is to empower individuals with diabetes by providing them with interactive tools for self-monitoring and data collection. The system employs non-invasive techniques for painless and routine blood glucose monitoring. The system is connected to the body through non-invasive sensors that detect blood glucose level. By gently attaching a finger to the MAX30102 photodetector sensor, blood glucose parameters are detected, with data seamlessly integrated into the Medicolink website. Users can access their health information via both the website and a smartphone application, facilitating real-time monitoring and informed decision-making.